Инновационные технологии на уроках английского языка - Утегенова, Г.Ж.; Джесова, Е.В. (My University, 2016)
This article represents a brief description of English teacher’s own experience in employing computer assisted and the most effective methods of teaching a foreign language. Application of informative in teaching of English helps to pick up methodical facilities and receptions that allow to diversify the forms of work and do a lesson interesting for students. On the lessons of English by means of innovative technologies it is possible to decide a number of didactic tasks : to form skills and abilities of reading, using materials of global network; to perfect abilities of writing speech of students; to fill up the vocabulary of students; to form at student motivation to the study of English.
Keywords: information technologies; effective method; methodical facilities and receptions; the internet is resources